Investigation Of OLED Performance In Non-Operated Mode Subjected To High Thermal Stress And Hygrothermal Aging - Mohammad, Muhammad Azrain (2019)
The attention towards organic light emitting diodes (OLEDs) has remarkably increased in recent years due to numerous advantages offered. However, the degradation issues responsible for the short lifetime of the devices, particularly after being exposed to high temperature and humidity has yet to be hlly established, even with the invention of encapsulation layers. The root cause of OLED degradations may also be diverse, and hence, involving the outcomes and failure mechanisms. Therefore, a comprehensive knowledge on this particular subject is essentially important as it is the key to unravel the short lifetime issues of OLEDs. Hence, the main purpose of this research is to study the OLED performance subjected to high thermal stress and hygrotherrnal effect, specifically via non-operated mode. Nonetheless, an optimum discharge time must first be acquired to ensure that the parasitic capacitance (due to thin structure of the OLEDs) can be fully eliminated for the purpose of data validity. In this study, a batch of commercially-available OLEDs has been employed. An onloff cycles approach was employed in which the OLED samples were switched-on (Ton) and -off (To&) at a specific time in determining the optimum discharge time. For high thermal test, the OLEDs were subjected to several temperatures in a controlled oven, including temperatures higher than the glass transition temperature (Tg) of the polymer material (-126 "C). Whilst in the hygrothermal aging test, the OLEDs were exposed to 85 OC and 85% RH in a humidity chamber at: different exposure time. A black box and a chroma-meter were used to monitor the changes in the luminance and voltagedrop values, while an interlayer analysis was performed by using focused ion beam (FIB) and field emission scanning electron microscope (FESEM) equipment. For this particular OLED, the optimum discharge time was found to be at Toff40 S. AS for high thermal test, it was observed that the luminance value has dramatically dropped by 90% fiom the initial value after the OLEDs were stressed at 135 OC, while the voltage-drop greatly escalated fiom 8.5 V to 30.2 V. The presence of voids between the layers were also evident due to the interfacial thermal stress. The voids have allowed the infiltration of moisture and oxygen into the device and eventually led to the formation of bubble-like defects on top of the cathode's surface. This condition has resulted in deterioration of electrons injection path and permanently changed the morphological structures of the devices. Through calculations, it was verified that the interfacial thermal stress between the layers can be reduced about 50% as the thickness of the polymer layer was increased by two times of its initial dimension. While in hygrothermal aging test, two primary modes of failure were observed. The first process involves the formation of centered-burst defects, and the second mode is the ringshaped delamination of cathode film. Essentially, both failure modes have destroyed the entire aluminum film and permanently changed the morphological surface of the device which has led to the total failure of the device. As a conclusion, the findings of this study profoundly emphasized on the performance and failure behaviors in OLED under extreme conditions, specifically via non-operated mode.